DeTEcT: dynamic and probabilistic parameters extension - Sadykhov, R.; Goodell, G.; Treleaven, P. (Frontiers in Blockchain, 2025)
This paper presents a theoretical extension of the Decentralized Token Economy Theory (DeTEcT) framework proposed by Sadykhov et al. (Front. Blockchain, 2023, 6, 1298330), where a formal analysis framework was introduced for modelling wealth distribution in token economies. DeTEcT is a framework for analysing economic activity, simulating macroeconomic scenarios, and algorithmically setting policies in token economies. This paper proposes four ways of parametrizing the framework, where dynamic vs. static parametrization is considered along with the probabilistic vs. non-probabilistic parameters. Using these parametrization techniques, we demonstrate that by adding restrictions to the framework, it is possible to derive the existing wealth distribution models from DeTEcT. In addition to exploring parametrization techniques, this paper explores how money supply in the DeTEcT framework can be transformed to become dynamic and how this change will affect the dynamics of wealth distribution. The motivation for studying dynamic money supply is that it enables DeTEcT to be applied to modelling token economies without maximum supply (i.e., Ethereum) and it adds constraints to the framework in the form of symmetries.